An Energetic Triazolo‐1, 2, 4‐Triazine and its N‐Oxide. Issue 49 (9th November 2016) - Piercey, Davin G.; Chavez, David E.; Scott, Brian L.; Imler, Greg H.; Parrish, Damon A.
Abstract: The reaction of 3‐amino‐5‐nitro‐1, 2, 4‐triazole with nitrous acid produces the corresponding diazonium salt. When the diazonium salt is treated with nitroacetonitrile, a subsequent condensation and cyclization reaction occurres to produced 4‐amino‐3, 7‐dinitrotriazolo‐[5, 1‐ c ][1, 2, 4] triazine (DPX‐26). X‐ray crystallographic analysis shows that the DPX‐26 has a density of 1.86 g cm −3, while it is calculated to have a heat of formation of 398.3 kJ mol −1 . DPX‐26 is predicted to approach the explosive performance of RDX but displays significantly better safety properties. Oxidation of DPX‐26 using hypofluorous acid produces 4‐amino‐3, 7‐dinitrotriazolo‐[5, 1‐ c ][1, 2, 4] triazine 4‐oxide (DPX‐27), which is also predicted to be a high‐performance material with enhanced safety properties. Abstract : Safety first : Reaction of 3‐amino‐5‐nitro‐1, 2, 4‐triazole with nitrous acid, followed by treatment with nitroacetonitrile, leads to DPX‐26. Oxidation of DPX‐26 using hypofluorous acid produces DPX‐27 (see X‐ray structure). Both DPX‐26 and DPX‐27 are predicted to be high‐performance energetic materials with enhanced safety properties.